Has exogenous melatonin induce histological changes in collecting tubules and ducts of rat’s kidney? - Ibraheem, Mustafa Mohammed; Alabbassi, Mustafa Ghazi; Abedali, Ali (AL-Kindy College Medical Journal, 2022)
Back ground; Selective re-absorption and secretion are the functions of the collecting tubules and ducts, in addition to concentrate urine through ADH-regulated and ADH-independent water channels.Method; twenty four male rats were used, they were divided into two groups of animals: Group (A) included twelve rats of five weeks old age (before puberty) that were divided into three subgroups, four rats in each subgroup. Subgroup I was control one, subgroups II and III were treated orally with melatonin in a dose of 250 & 500 µg/kg body weights subsequently. Group (B) included twelve rats of seventeen weeks old age (after puberty) that were divided into the same subgroups and treated with the doses of melatonin as in the rats of group (A).Result; the exogenous melatonin induced structural changes on the collecting tubules, in dose dependent manner as well as onset-dependent manner whether used in pre- or post-puberty of male albino rats